Mutations in the ERCC2 (XPD) gene associated with severe fetal ichthyosis and dysmorphic features. (2nd December 2016) - Miguet, Marguerite; Thevenon, Julien; Laugel, Vincent; Lefebvre, Mathilde; Bourchany, Aurélie; Rivière, Jean‐Baptiste; Duffourd, Yannis; Schaefer, Elise; Antal, Maria Cristina; Abida, Rosalie; Weingertner, Anne‐Sophie; Kremer, Valérie; et al.
Abstract : What's Already Known About This Topic? Congenital ichthyosis is a condition that includes several distinct subtypes with significant genetic heterogeneity. Defects in the ERCC2 [ xeroderma pigmentosum (XP) complementation group D ] gene lead to one of several clinical diseases, including XP, trichothiodystrophy, cerebrooculofacioskeletal syndrome, XP/Cockayne syndrome, and XP/trichothiodystrophy. What Does This Study Add? This observation enlarges the phenotypic spectrum of ERCC2 ( XP complementation group D ) mutations to severe fetal cases and expands the molecular basis of congenital ichthyosis by reporting the prenatal expression of a very rare nucleotide excision repair‐related condition.